Flow Cytometric Analysis of Red Blood Cell Osmotic Fragility. (October 2014) - Yamamoto, Ayako; Saito, Norihiro; Yamauchi, Yumiko; Takeda, Masahide; Ueki, Shigeharu; Itoga, Masamichi; Kojima, Keiya; Kayaba, Hiroyuki
This study investigated a new method of flow cytometry (FCM) for analysis of red blood cell (RBC) osmotic fragility. Venous peripheral blood collected in a sampling tube coated with EDTA 2Na was analyzed using FCM to determine RBC osmotic fragility. RBCs were represented as a double-peaked forward scatter (FSC) histogram in FCM. RBCs showed ballooning and spherical shape change in hypotonic solutions before hemolysis. The ballooning of RBCs was expressed as a disappearance of the minor peak and by narrowing and a shift to the right of the FSC histogram. The process of hemolysis was expressed as shrinking of the RBC cytogram in the right upper quadrant on the scatter plot of side scatter versus FSC and by emergence of a cell debris cytogram in the left lower quadrant. The ratio of intact RBCs in hypotonic solution was available as an indicator of osmotic fragility. Acidic solution made erythrocytes less tolerant to hypotonic solution by inducing spherical shape change. In conclusion, FCM can be used to assess RBC osmotic fragility.